Achyranthes bidentata Polysaccharide Activates Nuclear Factor-Kappa B and Promotes Cytokine Production in J774A.1 Cells Through TLR4/MyD88 Signaling Pathway - Fan, Sairong; Wang, Yanxing; Zhang, Yue; Wu, Yamin; Chen, Xiaoming (Frontiers in Pharmacology, 2021)
Achyranthes Bidentata Blume, a traditional Chinese medicine, is widely acknowledged for its function of invigorating livers and kidneys, stranguria-relieving diuretic, and used in the treatment of edema, gonorrhea and other diseases. A. bidentata polysaccharide (ABPS), isolated from A. bidentata, has been demonstrated to have multiple biological activity including immunomodulatory effects. However, the mechanisms underlying the effects of ABPS have not been fully investigated. The present study is conducted to explore the underlying mechanism of immunomodulatory activities of ABPS. Results showed that ABPS significantly increased the secretion of IL-1 and TNF- in J744A.1 cells. Nitric oxide (NO) also significantly increased after ABPS treatment. The special antibodies (Toll-like receptors 4 (TLR4) antibody, CD14/TLR4 antibody) significantly decreased the activation, while the Toll-like receptors 2 (TLR2) antibody couldn’t abolish this activation. Meanwhile, pyrrolidine dithiocarbamate (PDTC), a specific inhibitor of NF-B, remarkably inhibited the secretion of IL-1 and TNF- induced by ABPS in J744A.1 cells. Western blotting (WB) and confocal laser scanning microscope (CLSM) showed that ABPS promoted NF-B translocation into the nucleus. Furthermore, the mRNA and protein expression of TLR4 and MyD88 were significantly increased after ABPS treatment. Taken together, these findings suggested that the immunomodulatory mechanism of ABPS was associated with the secretion of cytokines by stimulating NF-B pathway through TLR4/MyD88 signaling.